2008
DOI: 10.1002/fld.1834
|View full text |Cite
|
Sign up to set email alerts
|

Healing of shock instability for Roe's flux‐difference splitting scheme on triangular meshes

Abstract: SUMMARYHealing of nonphysical flow solutions and shock instability from the use of Roe's flux-difference splitting scheme is presented. The proposed method heals nonphysical flow solutions such as the carbuncle phenomenon, the shock instability from the odd-even decoupling problem, and the expansion shock generated from the violated entropy condition. The performance and efficiency of the proposed method are evaluated by solving several benchmark and complex high-speed compressible flow problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Moreover, they made clear that there are at least two causes of the shock anomalies: one of these is a one-dimensional (1D) effect and the other is MD. The former appeared to be alleviated by adding (1D) dissipation to the shock-normal direction; whereas the latter could usually be suppressed by MD dissipation in the shock-perpendicular (transverse) direction [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they made clear that there are at least two causes of the shock anomalies: one of these is a one-dimensional (1D) effect and the other is MD. The former appeared to be alleviated by adding (1D) dissipation to the shock-normal direction; whereas the latter could usually be suppressed by MD dissipation in the shock-perpendicular (transverse) direction [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…And the grid at the mid-channel is perturbed alternatively at odd and even points with a small magnitude of ±10 −6 . For the Roe's FDS and the HLLC schemes, this grid is perturbed sufficiently to cause numerical instabilities so-called carbuncle phenomenon [6,7,10]. Figure 1 shows density contours at the three different positions…”
Section: Mach 6 Shock Moving Toward a Ductmentioning
confidence: 99%
“…Unfortunately, these schemes have some weaknesses and may produce numerical instabilities—including the sonic glitch, carbuncle phenomenon, and spurious oscillation—for certain problems, especially in hypersonic flow simulations 7‐9 . The sonic glitch phenomenon may arise when using the original Roe scheme in the presence of sonic rarefaction waves due to a disparity in wave speeds across the sonic point 10‐12 . A drawback of the Roe scheme is that it has to choose between normal compression shocks and expansion shocks.…”
Section: Introductionmentioning
confidence: 99%
“…The grid alignment and high grid aspect ratio usually influence the carbuncle phenomenon. Very elongated grids normal to the shock may enhance numerical instabilities leading to the anomaly 9,11,12 . Robinet et al 14 concluded that the carbuncle phenomenon was a pure numerical mechanism, so it should happen on certain unstructured grids.…”
Section: Introductionmentioning
confidence: 99%